The genetics of pain - Mogil, Jeffrey S. (Henry Stewart Talks, 2009)
Variability in pain sensitivity and analgesia, Heritability of pain, Genetic and environmental contributions to pain, Pain genes, Monogenic pain disorders, Association studies, Inbred mouse strains and strain differences, Genetic correlations among pain phenotypes, Quantitative trait loci (QTLs), Melanocortin-1 receptors and pain, Formalin test QTLs, Haplotype mapping, Atp1b3 and formalin pain